An analysis of the impact of urban married women's employment on household consumption - Lyu, Jiude; Soh, Wei Ni; Kharuddin, Saira (Universidad de Almera, 2023)
The realistic problem of the continuous downturn of Chinese residents' consumption has a long history. The tsunami like covid-19 has further worsened the consumption situation of the Chinese people. Using the questions and contents of the "Japan Household Panel Survey" (JHPS) questionnaire of Keio University, and taking the employment rate of other married women with the same income level in the same community as a tool variable, this paper empirically examines the impact of urban married women's employment on household consumption. The results show that the employment of married women in cities and towns significantly increases household consumption; Through the verification of the mechanism, it is found that the increase of total household income and the increase of marginal propensity to consume are important mechanisms for married women to obtain employment to promote urban household consumption, in which the increase of income plays a greater role in the improvement of low-income household consumption, and the increase of marginal propensity to consume plays a greater role in the improvement of high-income household consumption; The employment of married women has a positive impact on all kinds of household consumption, but it plays a greater role in promoting developmental consumption.